The best book of Harvard Graphics - Mueller, John, 1958- 4 0 16; 5 (Carmel, Ind. : Sams, 1991)
A guide to creating business charts and graphs using version 2.3. Includes a 5 1/4 inch disk of sample graphics.
System requirements for computer disk: IBM compatible XT-model PC (or better); 512K RAM; DOS 2.1 or higher; Harvard graphics program; hard disk with 6.5MB free space; CGA, EGA, VGA, or Hercules monochrome display board with compatible monitor; IBM- or Microsoft-compatible mouse or Kurta tablet (highly recommended to use DrawPartner); printer, plotter, or film recorder.;Includes index.
Keywords: 2 -- 0; 6; Harvard graphics (Computer file); Harvard graphics (Computer program);Computer graphics; 20; 2